Analysis of The Effectiveness of School Principles’ Democratic Leadership in Improving Teacher Professionalism - Ali, Jubair; Rino Vanchapo , Antonius; Suharyatun , Suharyatun; Subasman , Iman (Mudir : Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to ascertain whether democratic leadership among school principals increases teacher professionalism. In an effort to enhance teacher performance, including professionalism, school principals employ democratic leadership. Research of this kind is qualitative and employs descriptive qualitative research techniques. The methods employed to gather research data were observation, documentation study, and interviews with teachers, vice principals, and school principals. The data is described, followed by analysis, after the author has obtained the information, they need. The findings of the study suggest that the democratic leadership of school principals in fostering teacher professionalism is working quite well. The strategies undertaken include giving rewards, teacher discipline, coaching and training, high trust in subordinates, scheduled planning for professional development, interventions in management, and the learning process.